The Influence Of Brand Image, Promotion, And Price On Shopee Customer Loyalty (Case Study On Shopee Customers In Karawaci) - WasesoSegoro; Sandra Restu Aulia (International Journal of Science, Technology & Management, 2021)
Along with the times, people's lifestyles are increasingly instantaneous because the majority of people have high mobility in their daily activities. So that people are often looking for something practical and instantaneous in meeting their daily needs. Customer loyalty to voluntarily and continuously subscribe to certain companies for a long period of time. This study analyzes brand image , promotion, and price because these three factors play an important role in Shopee customer loyalty. The analytical tools used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, T test (partial), F test (simultaneous) and determination coefficient test using SPSS version 2.0 for windows. . The data used are primary data, the respondents in this study were 100 respondents, the sampling technique used was accidental sampling technique .The results showed that partially brand image, promotion, and price have a significant effect on customer loyalty. And simultaneously brand image, promotion, and price have a significant effect on Shopee customer loyalty.